(Invited) Progress and Challenges of AlGaN Schottky Diodes Grown on AlN Substrates. (17th August 2017) - Dalmau, Rafael; Craft, Hughes Spalding; Schlesser, Raoul; Mita, Seiji; Smart, Joseph; Hitchcock, Collin; Pandey, Gyanesh; Chow, Tat-Sing Paul; Moody, Baxter
Abstract : Quasi-vertical, high Al composition AlGaN Schottky diodes with breakdown voltages up to 500 V were grown on high quality AlN single crystal substrates. Diodes exhibited a 10 6 current rectification ratio, a 7 MV/cm peak field at blocking, and a 1.45 MW/cm 2 unipolar figure of merit. Challenges for this emerging technology, including doping limitations and compensation in AlGaN alloys, Ohmic contacts, and device termination are discussed.